APPROACHES FOR CHEMICAL SYNTHESIS AND DIVERSE PHARMACOLOGICAL SIGNIFICANCE OF PYRAZOLONE DERIVATIVES: A REVIEW - Asif, Mohammad (Journal of the Chilean Chemical Society, 2021)
Pyrazolone is a five-membered lactam ring containing two Nitrogens and one ketonic group in its structure. Numerous pyrazolone derivatives were exhibited with diverse biological, pharmacological, and chemical applications. When pyrazolones were discovered, they were only known as NSAIDs but in recent times they play a versatile role in several complications like cerebral ischemia, cardiovascular diseases, antibacterial, antioxidant, anticancer and several other pharmacological activities. Over the last few decades, pyrazolone derivatives have been used for various biochemical applications. Some of these derivatives such as metamizole, phenazone, aminopyrine, and propyphenazone, are widely used as anti-inflammatory and analgesics. The chemistry of pyrazolone has gained increasing attention due to its diverse pharmacological properties such as anticancer, analgesic, anti-inflammatory, antimicrobial, antioxidant, antifungal, antiviral, antidiabetic, and several other biological activities. Thus, keeping because of their importance, synthetic strategies for existing as well as novel pyrazolone derivatives have been developed and explored their biochemical utility. This review deals with the various pharmacological properties of different pyrazolone derivatives and puts chemical synthetic schemes.